Autophagy is essential for optimal translocation of iron to seeds in Arabidopsis. (4th November 2018) - Pottier, Mathieu; Dumont, Jean; Masclaux-Daubresse, Céline; Thomine, Sébastien
Abstract : Autophagy is an essential recycling mechanism making micronutrients available in vegetative organs for subsequent reallocation to seeds Abstract: Micronutrient deficiencies affect a large part of the world's population. These deficiencies are mostly due to the consumption of grains with insufficient content of iron (Fe) or zinc (Zn). Both de novo uptake by roots and recycling from leaves may provide seeds with nutrients. Autophagy, which is a conserved mechanism for nutrient recycling in eukaryotes, was shown to be involved in nitrogen remobilization to seeds. Here, we have investigated the role of this mechanism in micronutrient translocation to seeds. We found that Arabidopsis thaliana plants impaired in autophagy display defects in nutrient remobilization to seeds. In the atg5-1 mutant, which is completely defective in autophagy, the efficiency of Fe translocation from vegetative organs to seeds was severely decreased even when Fe was provided during seed formation. Combining atg5-1 with the sid2 mutation that counteracts premature senescence associated with autophagy deficiency and using 57 Fe pulse labeling, we propose a two-step mechanism in which Fe taken up de novo during seed formation is first accumulated in vegetative organs and subsequently remobilized to seeds. Finally, we show that translocation of Zn and manganese (Mn) to seeds is also dependent on autophagy. Fine-tuning autophagy during seed formation opens up new possibilities to improve micronutrient remobilization to seeds.